Assessment of Knowledge on Glaucomatous Disease in People with Glaucoma and Healthy Patients - Pedro Henrique Ogata Kodama; Rodrigo Toledo Mota; Deborah dos Santos Musich; Arthur Gustavo Fernandes; Mariana Gameiro Ierardi; Leonardo Amarante Pereira; Glaucia Luciano da Veiga; Beatriz da Costa Aguiar Alves; Vagner Loduca Lima; Fernando Luiz Affonso da Fonseca (European Scientific Journal, ESJ, 2025)
Background: Glaucoma is a chronic, irreversible optic nerve neuropathy characterized by loss of visual field, which can evolve to irreversible vision loss if not treated properly. This study aims to assess the level of knowledge about glaucoma between a group of diagnosed patients and a control group. Methods: 50 individuals with glaucoma (group A) of the Ophthalmology service of Centro Universitário FMABC were required to answer a validated questionnaire. 50 patients without diagnosed glaucoma (Group B) answered the same questionnaire. Sociodemographic data were recorded, a source of information on the disease of 50 patients in Group A and 50 in Group B and, in Group A, it was also asked for how long they had been diagnosed. Results: In the glaucoma group, 52% were female and 48% were male. In the control group, 66% were women and 34% were men. The mean age of group A was 66.4 years and that of group B was 55.7 years. All individuals with glaucoma reported being aware of the disease, while 23% of Group B lacked awareness of the disease. 54% of Group A patients were not aware that vision loss in glaucoma is slow and 46% of them reported that the disease is mostly associated with ocular discomfort. The mean score of the questions in Group A and Group B was 12.08 and 10.66, respectively (p=0.0098). Conclusion: Patients with glaucoma demonstrate greater awareness of the disease than participants without glaucoma but appear to lack awareness of the complications of this disease. This study suggests the need to improve the population's knowledge about the disease and the prevention of irreversible vision loss.